PENGARUH LEVERAGE KEUANGAN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM (Studi Kasus : Perusahaan Property dan Real Estate Periode 2015-2018 di Bursa Efek Indonesia) - Febriani, Rina; Afrida, Afrida (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
The purpose of this study was to determine the effect of financial leverage, profitability and firm size on stock prices on Property and Real Estate companies listed on the Indonesia Stock Exchange Period 2015-2018. This type of research is a quantitative descriptive study, with a population of 61 companies with a sample of 31 companies.This research data collection techniques through documentation with a ratio scale, based on the calculation results of the SPSS program application from the T Test obtained DER variable with a value of Î² is (-0.063) with a significant value (0.664)> 0.05 with tcount> ttable or (-0.435) > (- 1,701) then H0 is rejected, ROA with Î² value is 0.514 with significant value (0.000) <0.05 with tcount> t table or 6.204> 1.701 then H0 is accepted, firm size with Î² value is (-0.671) with significant value (0.283) <0.05 with tcount> t table or (-1.078)> (-1.701) then H0 is rejected.Test Results F Significant probability F = 0,000 is smaller than 0.05 with Fcount> Ftable or 13,353> 2,960, so that this research independent variables jointly affect the dependent variable. The determinant coefficient obtained a result of 0.250.This means that the variable financial leverage, profitability and company size can explain the variable stock prices of companies Property and Real Estate by 25%, the rest can be explained by other variables not observed in this study.